Kemampuan Metakognitif dan Komunikasi Matematis dalam Pemecahan Masalah Matematika - Sutini Sutini (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2019)
This descriptive qualitative study aims to describe the metacognitive and communicative abilities of the third-semester students of Mathematics Education of UIN Sunan Ampel Surabaya. Forty students were given a test consists of 2 essay problems of number theory. Three of the answer sheets that each one representing students with high, medium, and low scores were analyzed. Findings show that the students' ability in both aspect are unsatisfactory regardless of their different scores. They are don't show their understanding of the concepts and principles of number theories, some of them still use mathematical terms and notes, and the majority still have the wrong calculation because they not use the complete and correct algorithm. The students' ability in mathematical communication is poor because they can't write the correct mathematical symbols and can't put the mathematical ideas in an acceptable, logical order. They have written the answers that seem to the right answers, but the arrangement of the answers is irrational and jumping, resulting in the answers in low comprehensibility.